OTME-8. Inhibitory CD161 receptor identified in glioma-infiltrating T cells by single-cell analysis. (5th July 2021) - Gritsch, Simon; Mathewson, Nathan; Ashenberg, Orr; Perez, Elizabeth; Marx, Sascha; Reardon, David; Regev, Aviv; Suva, Mario; Wucherpfennig, Kai
Abstract: T-cells are critical effector cells of cancer immunotherapies, but little is known about T-cell gene expression programs in diffuse gliomas. We leveraged single-cell RNA-seq to chart the gene expression and clonal landscape of tumor-infiltrating T-cells across 31 patients with isocitrate dehydrogenase (IDH) wild-type glioblastoma and IDH mutant glioma. Our analysis revealed subsets of T-cells that expressed several NK-cell receptors, in particular the inhibitory CD161 receptor ( KLRB1 gene). KLRB1 was overexpressed by clonally expanded CD8 T-cells, and larger populations of T-cells expressed CD161 than PD-1. The CLEC2D ligand of CD161 was expressed by malignant cells and myeloid cells, and inactivation of KLRB1 enhanced anti-tumor T-cell function. KLRB1 was also expressed by substantial T-cell populations in multiple other human cancers. CD161 and other NK-cell receptors expressed by T-cells represent opportunities for immunotherapy of diffuse gliomas and other human cancers.